Silencing Of The Polyamine Catabolic Key Enzyme SSAT Prevents CDK Inhibitor-Induced Apoptosis In Caco-2 Colon Cancer Cells - Çoker, Ajda; Palavan Ünsal, Narçin; ARISAN, ELİF DAMLA (Spandidos Publ Ltd, Pob 18179, Athens, 116 10, Greece, 2012)
Roscovitine and purvalanol are purine derivative cyclin-dependent kinase (CDK) inhibitors that induce apoptosis in various types of cancer cells. However, their impact on the apoptotic cell death mechanism requires further elucidation. Natural polyamines putrescine, spermidine and spermine play essential roles in the regulation of cell growth and proliferation. Increased levels of polyamines in cells are considered to be involved in cancer progression. Intracellular polyamine levels are under the control of several catabolic enzymes, such as spermidine/spermine-N-acetyl transferase (SSAT), acetylpolyamine oxidase (APAO) and spermine oxidase (SMO), which could be altered by several therapeutic drugs. However, the possible role of polyamines in drug-induced apoptosis has yet to be clarified. In the present study, our aim was to determine the modulation of the polyamine catabolic pathway related to CDK inhibitor-induced apoptosis in Caco-2 cells. We found that roscovitine and purvalanol (each 20 mu M) induced apoptosis by activating caspase-9 and -3, and inhibiting the mitochondrial membrane potential in Caco-2 cells. CDK inhibitors decreased the intracellular putrescine and spermine levels without affecting spermidine levels. Although both roscovitine and purvalanol induced SSAT expression, they did not exert a significant effect on the APAO expression profile. SSAT transient silencing prevented roscovitine-induced apoptosis compared to parental cells. Thus, we concluded that roscovitine and purvalanol significantly induce apoptosis in Caco-2 cells by modulating the polyamine catabolism, and that SSAT could be an important target in evaluating the potential role of polyamines in apoptotic cell death.
Keywords: roscovitine; purvalanol; cyclin-dependent kinase inhibitors; polyamines; spermidine/spermine-N-acetyl transferase; colon carcinoma; cyclin-dependent kinase; in-vivo; spermidine/spermine n-1-acetyltransferase; down-regulation; roscovitine; purvalanol; combination; spermine; therapy; potent; Sikline bağımlı kinaz önleyicileri; poliaminler; Spermidin / spermin-N-asetil transferaz; kolon karsinoması; siklin bağımlı kinaz; Spermidin / spermin n-1-asetiltransferaz; indirgeme; kombinasyon; terapi; güçlü